2014
DOI: 10.1371/journal.pone.0089236
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Producing B Cells Are Induced Early in HIV-1 Infection and Suppress HIV-1-Specific T Cell Responses

Abstract: A rare subset of IL-10-producing B cells, named regulatory B cells (Bregs), suppresses adaptive immune responses and inflammation in mice. In this study, we examined the role of IL-10-producing B cells in HIV-1 infection. Compared to uninfected controls, IL-10-producing B cell frequencies were elevated in both blood and sigmoid colon during the early and chronic phase of untreated HIV-1 infection. Ex vivo IL-10-producing B cell frequency in early HIV-1 infection directly correlated with viral load. IL-10-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 55 publications
6
89
4
2
Order By: Relevance
“…Therefore, it is not surprising that the phenotype of GraB cells (enhanced expression of GrB, IDO, CD5, CD10, CD43, CD86, and CD147) is only compatible, in part, with the various regulatory B cell phenotypes described elsewhere. Of note, a recent publication described a minor population of IL-10 + B cells in untreated HIV patients (38). In contrast, in the current study, we did not detect a significant difference in IL-10 expression between healthy B cells and GraB cells from HIV patients, and we found that T cell regulation by GraB cells occurred in an IL-10-independent manner (data no shown).…”
Section: Discussioncontrasting
confidence: 94%
“…Therefore, it is not surprising that the phenotype of GraB cells (enhanced expression of GrB, IDO, CD5, CD10, CD43, CD86, and CD147) is only compatible, in part, with the various regulatory B cell phenotypes described elsewhere. Of note, a recent publication described a minor population of IL-10 + B cells in untreated HIV patients (38). In contrast, in the current study, we did not detect a significant difference in IL-10 expression between healthy B cells and GraB cells from HIV patients, and we found that T cell regulation by GraB cells occurred in an IL-10-independent manner (data no shown).…”
Section: Discussioncontrasting
confidence: 94%
“…Increased IL-10 expression has been reported to be a strategy of several viral pathogens, such as HIV-1, rhinovirus and cytomegalovirus, to suppress host immune responses (Koponen et al, 2013;Liu et al, 2014;Loebbermann et al, 2012;Mason et al, 2013;Redpath et al, 2001). Upregulation of IL-10 could lead to the suppression of antigen-presenting-cell functions, including the production of pro-inflammatory cytokines (Redpath et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple subsets of B cells that produce IL-10, often with overlapping surface markers but diverse functions, have been reported and are collectively referred to as Bregs (12 + B cells, which have all been shown to suppress proinflammatory responses (4,(13)(14)(15)(16). Notably, fewer than 20% of the B cells within these different B cell subsets produce IL-10 and suppress immune responses.…”
Section: Mechanism Of Suppressionmentioning
confidence: 99%